The effect of depth and sowing time on germination, yield and yield components of naked and hulled oat - Pacewicz, Krzysztof; Stankowski, Slawomir (MTT, 2004)
The first hulless cultivar Akt was taken into regional distribution in Poland in 1997 and the next one Polar in 2002. Earlier results with the naked cultivars showed that in the field conditions the germination was reduced. Our aim was estimate the influence of the agrotechnical factors on the germination dynamics, grain yield and the yield components of the naked oat variety Akt. Field experiments were conducted in Agricultural Experimental Station Lipnik near Stargard Szczecinski, during 2001-2003 using 2 sowing dates (optimal and 2 weeks later), 2 varieties of oat (naked Akt and hulled Bajka), 4 sowing depths (1, 3, 5, 7 cm). Delay of sowing time did not have a significant influence on number of plants after germination, except in 2003. Depending on the vegetation season the field germination of naked cultivar Akt was lower than hulled cultivar Bajka. Both cultivars were more tolerant of too deeper sowing depth than too lower sowing depth. Two weeks delay of sowing time caused significant decrease in grain yield mainly due to lower grain number in panicle and slightly decrease weight of 1000 grains. Number of panicles per square meter were similar independently on sowing time. Like in Budzyñski et al. (1999) the changes of the sowing depth in comparison with recommended depth 3cm caused that the grain yield was decrease up to 10% due to lower number of panicles per square meter. The obtained differences were not similar depending on sowing time and depth in each year of researches. Naked cultivar Akt yielded up to 27% lower comparing to hulled cultivar Bajka, but the differences fluctuated from 33 to 24% depending on vegetation season. The yield difference between cultivars resulted from lower weight of 1000 grains of the naked oat. Naked oat has lower panicle number per square meter at optimal sowing time. Naked cultivar obtained higher grain number than hulled Bajka per panicle. Also Peltonen-Sainio (1994) found naked lines to produce less panicles per square meter and increased the number of grains per panicle, Contrary to Cermak & Moudry (1998). Budzyñski, W. et al. 1999. ¯ywno æ. 1(18) Suppl.: 99-103; Cermak, B. & Moudry, J. 1998. Acta Acad. Agricult. Tech. Olst. 66: 89-98; Peltonen-Sainio P. 1994. Agronomy Journal 86: 510-513.
Keywords: Ka; sowing time; sowing depth; hulled and naked oat; yield; yield components